Functional-Typological Analysis of Grammatical Relations and Semantic Roles in Minangkabau Language - Riskia Sitti Velini; Adnania Nugra Heni; Ayu Hudzaifah; Pangeran Muhammad Faqih Syafaat; Irfa Luthfia Rahmani; Nadya Ramadhanty (Universitas Bengkulu, 2026)
Functional typology focuses on clause structure and argument relations as they contribute to meaning. The purpose of this research is to characterize the Minangkabau language's grammatical relationships and semantic roles of subjects and objects. The study uses a literature-based methodology and a qualitative descriptive method. The data were taken from Minangkabau folktales and consists of 80 basic clauses. In order to ascertain syntactic behavior, the analysis employs subjecthood tests (raising, reflexive control, relativization, and quantifier float) in addition to identifying grammatical relations and semantic roles. The results show that Minangkabau subjects continuously hold the greatest syntactic position, regardless of whether they behave as agents or non-agents. Subjects can appear before the predicate, influence reflexive noun phrases, and be relativized. However, objects are different from subjects. Direct objects function as dative or benefactive semantically, whilst indirect objects function as patient. Grammatical relations and semantic roles interact hierarchically and functionally in phrase structure, as demonstrated by Minangkabau's typological nominative–accusative alignment with a simple S–V–O word order.